The "Sorondrano" rain ritual: perception and driving forces of actors in the face of climatic variability in southern Madagascar - Rasolondraizafy, Jean Fidison; Ramananarivo, Romaine; Razafindraibe, Rolland; Ranaivoson, Rado Elysé (Technium Social Sciences Journal, 2022)
This paper aims to analyze the manifestation of the “Sorondrano” rain ritual and to assess community perceptions of its expected impacts in the face of extremely dry years over the past 38 years. Specifically, it attempts to characterize the relationship of the Ntandroy to their history and their ways of controlling their environment through this ritual practice and to highlight the conditions and requirements, norms and principles applicable to make the success of the ritual activity effective and reassuring in cases of repetitive droughts. The ethnographic field study was conducted with 44 respondents who had not left the localities in the past 10 years and were selected by purposive sampling. Data was further analyzed qualitatively by content analysis given the prevalent use of Likert type scales analyses. The surveys showed that the majority of the participants have witnessed the ritual ceremony in their lives and affirm its notoriety. They perceived its performance in the face of the eight cases of climatic drought recorded from 1981 to 2019, fitting in the harmonization of procedural steps that the sacrifice is performed without any error. The results imply the continued engagement in the Community - Supernatural Being relationship for the sustainable management of climatic drought cases and above all support the Ntandroy social religion as true coping strategies promoting rainfall as a local economic revival.